2010
DOI: 10.1177/1947603510381096
|View full text |Cite
|
Sign up to set email alerts
|

Acute Osteoclast Activity following Subchondral Drilling Is Promoted by Chitosan and Associated with Improved Cartilage Repair Tissue Integration

Abstract: Objective:Cartilage-bone integration is an important functional end point of cartilage repair therapy, but little is known about how to promote integration. We tested the hypothesis that chitosan-stabilized blood clot implant elicits osteoclasts to drilled cartilage defects and promotes repair and cartilage-bone integration.Design:Bilateral trochlear defects in 15 skeletally mature rabbit knees were microdrilled and then treated with chitosan–glycerol phosphate (GP)/blood implant with fluorescent chitosan trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 55 publications
7
60
0
Order By: Relevance
“…From a clinical standpoint, the present study and previous investigations in small animal models192243 show that the balance of bone turnover is clearly shifted to bone resorption at this very early phase, the first several weeks of cartilage repair following microfracture. The finding of the present study that osteoclast density is higher in both microfracture groups compared with debridement alone is in good agreement with the work of Chen et al ., supporting the important role of osteoclasts as cellular mediators of marrow stimulation techniques that incise the subchondral bone22.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…From a clinical standpoint, the present study and previous investigations in small animal models192243 show that the balance of bone turnover is clearly shifted to bone resorption at this very early phase, the first several weeks of cartilage repair following microfracture. The finding of the present study that osteoclast density is higher in both microfracture groups compared with debridement alone is in good agreement with the work of Chen et al ., supporting the important role of osteoclasts as cellular mediators of marrow stimulation techniques that incise the subchondral bone22.…”
Section: Discussionsupporting
confidence: 66%
“…Hoemann et al . proved that new bone formation already started at 2 weeks following the marrow stimulation in a rabbit model, accompanied by a high activity of osteoclasts, serving as cellular mediators of marrow-derived cartilage repair22. However, the very early effects of microfracture on the subchondral bone in a large animal model remain unknown to date.…”
mentioning
confidence: 99%
“…Previous studies have shown that a higher level of bone remodeling activity is one of the main factors supporting improved cartilage repair during stimulation of the repair process using biomaterials. 4,5,8,17,18 The presence of a remodeled and porous subchondral bone plate was also previously associated with more hyaline tissue repair and Figure 5. Characterization of the extent of repaired and remodeling subchondral bone in trochlear defects that received marrow stimulation.…”
Section: Discussionmentioning
confidence: 95%
“…Bone marrow cells are also altered by smoking, and aging, which could also limit the repair response to MFX. 5,22,26,44 Our data suggest that uniform debridement of approximately 200 µm of mineralized tissue should be sufficient to remove the calcified cartilage layer in most lesions, including Grade IV lesions. Curettage offers a tactile appreciation of the "grating" away of mineralized tissue but is time-consuming, nonuniform, and can lead to iatrogenic damage of surrounding cartilage.…”
Section: Discussionmentioning
confidence: 93%